Influence of microfillers on molecular alignment and tensile stress fracture in thermotropic liquid crystalline polymer. Issue 3 (June 2012) - Romo-Uribe, Angel; Flores, Osvaldo; Campillo, Bernardo; Flores, Araceli; Jaffe, Michael
Abstract : This research focuses on the influence of microfillers on mechanical properties, molecular orientation, and fracture behavior of reinforced thermotropic liquid crystalline polymers (LCPs). The LCPs are random copolyesters based on 1, 4-hydroxybenzoic acid (B) and 2, 6-hydroxynaphthoic acid (N) with composition 73:27 mol%. Glass fibers, graphite, and mineral fillers were used as microfillers. The influence of filler was investigated, up to 30 wt % filler concentration. Tensile tests revealed that the strain at failure of the neat LCP occurred within 3% deformation. The addition of microfillers initially decreased the Young's modulus and the strain at failure below that of the neat LCP. However, the combination of graphite/glass fibers did increase the Young's modulus, and increased the yield stress but at the cost of reducing, significantly, the strain at failure. The x-ray patterns of the molded neat LCP showed that the molecular chains were preferentially oriented along the injection molding axis. However, addition of microfillers randomized the molecular orientation, as measured by the order parameter, P–2, where glass fiber-based fillers were more effective to reduce P–2. The reduction in molecular alignment appeared to be the key property to deteriorate Young's modulus along the shear axis. Moreover, the reduction in modulus could be compensated by adding more microfillers and offers the benefit of homogenizing the mechanical properties. Analysis of fractured samples suggests that the main mechanism for fracture was the loss of adhesion between the microfillers and the polymer matrix, this effect being more evident when using glass fiber.